On the development of computer code for aircraft flight dynamics analysis - Mohamed Alazomui, Outman (2014)
The stability analysis of the aircraft can be evaluated in two flight modes: longitudinal stability analysis and the lateral – directional stability analysis. The present work focused on the second mode of flight. The stability analysis carried out by evaluates the behavior of three flight parameters if their aircraft control surfaces operated. These three flight parameters are the side slip angle β, the roll angle  and the yaw angle . These three parameters describe the aptitude of the aircraft which can be obtained through solving the governing equation of flight motion. In this respect, the governing equation of flight motion is the Lateral-Directional Flight Equation. To solve this equation, the present work use a Matlab programming language which allow to solution of the governing equation of flight motion carried out by use of a Laplace transformation. The stability analysis of the aircraft carried out over four type aircraft. The first two type of aircraft belong to class of a propeller driven aircraft, while the rests are the turbojet aircraft type of aircraft. The developed computer code provide 2 option how the aileron are deflected, they are namely (1) a single double impulse aileron and (2) a multiple doublet impulse aileron. While from the point of view rudder is also having two type of deflection, namely (1) a single double impulse rudder and (2) a multiple double impulse rudder. These types of control surfaces deflection applied to case of Cessna – 182, Beech – 99, Lear Jet – M24 and The Lockheed F104. The results indicate that each of aircraft has different response in anticipating with the deflection of aileron as well as rudder.